Engineering Planning and Digital Transformation in Smart Project Management: An Applied Study on Al-Nukhba Engineering General Contracting Company - عواطف على عبد السلام موسى; المهدي الباروني سالم خبريش (African Journal of Advanced Pure and Applied Sciences, 2025)
This study aims to analyze the current status of smart construction project management in Libya through an applied study at Al-Nukhba Construction Company, focusing on engineering planning, digital transformation, and their impact on performance. The study adopted a descriptive-analytical approach, and data were collected using a field questionnaire distributed to 50 employees from various engineering and managerial categories. The data were analyzed using SPSS to calculate the mean values and standard deviations. The results showed that the implementation level of smart management systems is relatively high, with an overall mean of 3.90, and a strong reliance on digital planning tools and schedule monitoring. The study also indicated that digital transformation contributed to improved communication and reduced delays, while challenges such as poor internet connectivity and insufficient technical training still affected performance effectiveness. The findings reflect that the company is moving towards digital transformation, providing opportunities to enhance project management efficiency and improve overall performance in the Libyan construction sector.